INCIDÊNCIA E DISTRIBUIÇÃO GEOGRÁFICA DE HIPERPLASIA ADRENAL CONGÊNITA EM GOIÁS ENTRE 2006 A 2012 - João Felipe Gomide de Paula Souza; Dante Carmo Correia Filho; Larissa Di Villeneuve Caetano Pereira Araújo; Antônio Rubens Alvarenga (UniEVANGÉLICA, 2015)
Objective: To identify the incidence and geographical distribution of congenital adrenal hyperplasia in the state of Goiás between 2006 and 2012. Methods: Quantitative, explanatory descriptive, documentary study, held at APAE-Anápolis in Goiás. The results of neonatal screening were searched from January 2006 to December 2012 in APAE Anápolis-Goiás. The criteria of inclusion were the neonatal screening examination between the third and the thirtieth day of life. Those who did not fit or whose tests were not with all the necessary data for the study were excluded. Data were collected through document analysis. The documents consisted of information contained in the results of laboratory tests of the Foot Test. The analysis was performed using the value of 17-hydroxy-progesterone dosed in the Foot Test. Tests above the reference range were separated and analyzed. Results: Were screened 542 407 newborns by APAE-Anápolis-Goiás, and there were 1,854 suspects. It was confirmed 50 newborns with the disease (31 male and 19 female). The cumulative incidence in the state was 1: 10,846. The cities of Rio Verde, Goiânia and Catalão had more cases in this period. Conclusions: The incidence of the disease in Goiás was within the expected range in the world, even with high rates in some cities. Compared with Brazil, Goiás had a smaller number of cases. Comparing the gender, there was more cases of disease affection between male newborns, diverging from the literature. The city with the highest incidence in the state was Rio Verde, not establishing a cause for this high rate.